Gyroscope‐Like Molecules Consisting of PdX2/PtX2 Rotators within Three‐Spoke Dibridgehead Diphosphine Stators: Syntheses, Substitution Reactions, Structures, and Dynamic Properties. Issue 16 (6th March 2014) - Nawara‐Hultzsch, Agnieszka J.; Stollenz, Michael; Barbasiewicz, Michał; Szafert, Sławomir; Lis, Tadeusz; Hampel, Frank; Bhuvanesh, Nattamai; Gladysz, John A.
Abstract Threefold intramolecular ring‐closing metatheses of trans‐[MCl2(P{(CH2)mCHCH2}3)2] are effected with Grubbs' catalyst. Following hydrogenation catalyzed by [RhCl(PPh3)3], the title complexes trans‐[<overline>MCl2(P((CH2)n)3P</overline>)] (n=2m+2; M/n=Pt/14, 4 c; Pt/16, 4 d; Pt/18, 4 e; Pd/14, 5 c; Pd/18, 5 e) and sometimes isomers partly derived from intraligand metathesis, trans‐[<overline>MCl2{P(CH2)n(CH2)n}P</overline>(CH2)n)] (4′c–e, 5′e), are isolated. These react with LiBr, NaI, and KCN to give the corresponding MBr2, MI2, and M(CN)2 species (58–99 %). 13C NMR data show that the MX2 moieties rapidly rotate within the diphosphine cage on the NMR timescale, even at −120 °C. The reaction of 4 c and KSCN gives separable Pt(NCS)2 and Pt(NCS)(SCN) adducts (13 c, 28 %; 14 c, 20 %), and those of 4 c, e and Ph2Zn give PtPh2 species (15 c, 61 %; 15 e, 90 %). 13C NMR spectra of 13 c–15 c show two sets of CH2 signals (ca. 2:1 intensity ratios), indicating that MX2 rotation is no longer rapid. Reactions of 4 c or 4′c and excess NaCCH afford the free diphosphines P{(CH2)14}3P (91 %) and (<overline>CH2)14P</overline>(CH2)14<overline>P(C</overline>H2)14 (90 %). The latter has been crystallographically characterized as a bis(BH3) adduct. The crystal structures of eight complexes with P(CH2)14P linkages (PtCl2, PtBr2, PtI2, Pt(NCS)2, PtPh2, PdCl2, PdBr2, PdI2) and 15 e have been determined, and intramolecular distances analyzed with respect to MX2 rotation. The conformations of the (CH2)14 moieties and features of the crystal lattices are also discussed.